Centriolar Protein C2cd3 Is Required for Craniofacial Development - Chang, Ching-Fang; Brown, Kari M.; Yang, Yanfen; Brugmann, Samantha A. (Frontiers in Cell and Developmental Biology, 2021)
The primary cilium is a ubiquitous, microtubule-based cellular organelle. Primary cilia dysfunction results in a group of disorders termed ciliopathies. C2 domain containing 3 centriole elongation regulator (C2cd3), encodes a centriolar protein essential for ciliogenesis. Mutations in human C2CD3 are associated with the human ciliopathy Oral-Facial-Digital syndrome type 14 (OFD14). In order to better understand the etiology of ciliopathies including OFD14, we generated numerous murine models targeting C2cd3. Initial analysis revealed several tissue-specific isoforms of C2cd3, and while the loss of C2cd3 has previously been reported to result in exencephaly, tight mesencephalic flexure, pericardial edema, abnormal heart looping and a twisted body axis, further analysis revealed that genetic background may also contribute to phenotypic variation. Additional analyses of a conditional allelic series targeting C-terminal PKC-C2 domains or the N-terminal C2CD3N-C2 domain of C2cd3 revealed a variable degree of phenotypic severity, suggesting that while the N-terminal C2CD3N-C2 domain was critical for early embryonic development as a whole, there was also a craniofacial specific role for the C2CD3N-C2 domains. Together, through generation of novel models and evaluation of C2cd3 expression, these data provide valuable insight into mechanisms of pathology for craniofacial ciliopathies that can be further explored in the future.